2023
DOI: 10.1038/s41431-023-01324-w
|View full text |Cite
|
Sign up to set email alerts
|

Skewed X-chromosome inactivation in unsolved neurodevelopmental disease cases can guide re-evaluation For X-linked genes

Abstract: Despite major technical and genetic advances, more than half of the neurodevelopmental disorders (NDDs) cases remain undiagnosed.We explored the frequency of non-random XCI in the mothers of male patients and in affected females from a clinically heterogeneous cohort of unsolved NDD cases, negative at FRAXA, chromosomal microarray analysis and Trio Exome Sequencing. We hypothesize that an unbalanced XCI could unmask previously discarded genetic variants on the X chromosome connected both to XCI and NDD.A multi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 41 publications
1
11
2
Order By: Relevance
“…A different study conducted in 2023, much like the 2003 study, found that doing more profiling and research into X chromosomes may help in identifying the causes of neurodivergent disorders and identifying other X-linked disorders. [10] This study suggests that there's an age and disorder-specific pattern in how a brain develops and changes which cause autism, although this study does not confirm whether it's specific to ASD or present in other neurodevelopmental disorders, even though that would be consistent with previous research.…”
Section: Early Signs and Diagnosis Of Asdcontrasting
confidence: 87%
See 1 more Smart Citation
“…A different study conducted in 2023, much like the 2003 study, found that doing more profiling and research into X chromosomes may help in identifying the causes of neurodivergent disorders and identifying other X-linked disorders. [10] This study suggests that there's an age and disorder-specific pattern in how a brain develops and changes which cause autism, although this study does not confirm whether it's specific to ASD or present in other neurodevelopmental disorders, even though that would be consistent with previous research.…”
Section: Early Signs and Diagnosis Of Asdcontrasting
confidence: 87%
“…[3] The study interestingly looked at Head Circumference (HC) at birth to be an early indicator of autism. [10] The first phase at birth showed that the average HC measurement is at the 25th percentile but was not accompanied by a decrease in prenatal body growth as the body length and weight at birth are not less than the values of healthy infants at birth. The study also found that brain volume decreases at birth appeared to be small and could not be used as a pre-onset indicator of autism in later years.…”
Section: Early Signs and Diagnosis Of Asdmentioning
confidence: 95%
“…The patients were divided into three categories (see Tables 1 and S1 ): (1a) validation cohort #1a, which consisted of 34 NDD cases with pathogenic or likely pathogenic single nucleotide variants (SNVs) in a gene with known disease-specific methylation patterns or episignatures that are listed in the EpiSign v.3 classifier; (1b) validation cohort #1b, which consisted of 25 NDD cases with pathogenic or likely pathogenic CNVs that are also listed in the EpiSign v.3 classifier; (2) an uncertain cohort composed of 18 NDD cases with an SNV/CNV VUS or with a strong clinical suspicion but no specific variant identified, and (3) 20 unresolved NDD cases defined by females or mothers of unresolved male cases that showed skewed X chromosome inactivation (XCI) of more than 80% (Supplemental Materials and methods). 17 …”
Section: Methodsmentioning
confidence: 99%
“…Such a situation has also been described for females with Duchenne muscular dystrophy [ 25 , 26 ]. Studying X-inactivation patterns in ID families with affected and unaffected female family members with XCI skewing in opposite directions, and often with affected males in the kindred, may identify variants whose causative nature was not initially recognized because it was also found in unaffected females [ 30 ].…”
Section: Random X-chromosome Inactivation In XX Individualsmentioning
confidence: 99%